THE PODIUM OF THE USE OF INNOVATIVE TECHNOLOGIES AIMED AT THE INDIVIDUAL IN THE EDUCATIONAL PROCESS - Musayeva Muhabbat Eshbayevna (European Science Publishing, 2024)
This scientific article presents methods for directing listeners to innovative activities in the system of professional development and methods of educational integration and the use of pedagogical technologies used in its implementation.